A Note on Capital Gains Exemption and Risk Taking - Ahsan, Syed M. (Quarterly Journal of Economics, 1975)
Journal Article A Note on Capital Gains Exemption and Risk Taking Get access Syed M. Ahsan Syed M. Ahsan McMaster University and The University of Western Ontario Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 89, Issue 1, February 1975, Pages 151–153, https://doi.org/10.2307/1881717 Published: 01 February 1975